2017
DOI: 10.1038/s41598-017-12804-7
|View full text |Cite
|
Sign up to set email alerts
|

Phyto-mediated metallic nano-architectures via Melissa officinalis L.: synthesis, characterization and biological properties

Abstract: The development of methods for obtaining new materials with antimicrobial properties, based on green chemistry principles has been a target of research over the past few years. The present paper describes the phyto-mediated synthesis of metallic nano-architectures (gold and silver) via an ethanolic extract of Melissa officinalis L. (obtained by accelerated solvent extraction). Different analytic methods were applied for the evaluation of the extract composition, as well as for the characterization of the phyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 57 publications
0
45
0
Order By: Relevance
“…The silver nanoparticles alone were also proven to be an efficient antimicrobial agent against bacteria and fungi developed on different materials (stucco, calcite and basalt), inhibiting the colonization of the stones (0.16%-3.6% colonization, compared with the untreated samples-8%-28% colonization, depending on the material) [74]. The authors observed a dependency on the AgNPs dose, and less on the NPs size (as is the case for the in vitro antimicrobial properties of the nanoparticles) [75,76].…”
Section: Nanotechnological Approachesmentioning
confidence: 98%
“…The silver nanoparticles alone were also proven to be an efficient antimicrobial agent against bacteria and fungi developed on different materials (stucco, calcite and basalt), inhibiting the colonization of the stones (0.16%-3.6% colonization, compared with the untreated samples-8%-28% colonization, depending on the material) [74]. The authors observed a dependency on the AgNPs dose, and less on the NPs size (as is the case for the in vitro antimicrobial properties of the nanoparticles) [75,76].…”
Section: Nanotechnological Approachesmentioning
confidence: 98%
“…Bi-metallic Au/Ag NPs have been proven to be efficient (in some cases even superior to Ag NPs) against a series of microbial and isolates lines. Their observation is surprising, as it would be expected bi-metallic NPs to show intermediate antimicrobial properties [80]. Similarly, Fe 3 O 4 /Cu NPs have been proven to retain both their magnetic properties (from the Fe 3 O 4 component) and antimicrobial properties (from the Cu NPs), with a minimum inhibitory (bactericidal) concentration (MIC/MBC) close to the ones obtained for Cu NPs against Gram-positive and Gram-negative bacteria [79].…”
Section: Au Npsmentioning
confidence: 99%
“…The qualitative screening of the antimicrobial properties was performed by an adapted spot diffusion method [36,37]. Bacterial and yeast suspensions of 1.5 × 10 8 CFU•mL −1 (corresponding with 0.5 McFarland standard density) obtained from 24-48 h microbial cultures developed on Muller Hinton agar (MHA) and Sabouraud agar (SA) media, were used in the experiments.…”
Section: Determination Of Antimicrobial Activitymentioning
confidence: 99%